Advancements in Laser and Ultrasound Therapeutic Strategies for Cancer Cells: Recent Review - Rasul, Raghad; Abduljabbar, Jamal; Khalil, Iman (Al-Nahrain Journal for Engineering Sciences, 2023)
Cancer is a disease caused by uncontrollable cell growth and division. Surgery, chemotherapy, radiotherapy, and hormonotherapy are all cancer treatment options. In addition to noninvasive cancer ablative therapy. As an example, ultrasonic therapy, even with low-intensity pulsed ultrasound (LIPUS) or high-intensity focused ultrasound (HIFU), and Laser therapy (photo-biomodulation therapy) in low-level laser therapy (LLLT) with different wavelength ranges from ultraviolet (UV), visible and infrared (IR) that all have demonstrated different results depending on the target of treatment so previous trials therapies are being studied. This paper reviews recent studies on the in vitro treatment effect of ultrasound therapy and laser therapy on normal and cancerous cell lines with specific parameters. The effect of ultrasound results showed a decrease in cell proliferation and an increase in apoptosis in different types of cells, depending especially on sound intensity, known as Special Peak Temporal Average Intensity (ISPTA). While the laser effect is noticed on cell viability, either enhance or inhibit their viability depending upon the dose of exposure and other specific parameters like wavelength, energy density, and power density used in each treatment protocol. The previous studies conclude that each response would have a treatment method with specific parameters, even an increase or decrease in cell viability. Further studies need to be applying these methods in vivo.